Gaps in Emergency General Surgery Coverage in the United States - Angela M. Ingraham, MD, MS; Scott M. Chaffee, BS; M. Didem Ayturk, MS; Victor K. Heh, PhD; Catarina I. Kiefe, MD, PhD; Heena P. Santry, MD, MS (Annals of Surgery Open, 2021)
Introduction:. Despite 3 million adults in the United States being admitted annually for emergency general surgery (EGS) conditions, which disproportionately affect vulnerable populations, we lack an understanding of the barriers to round-the-clock EGS care. Our objective was to measure gaps in round-the-clock EGS care. Methods:. From August 2015 to December 2015, we surveyed all US-based adult acute care general hospitals that have an emergency room and ≥1 operating room and provided EGS care, utilizing paper and electronic methods. Surgeons or chief medical officers were queried regarding EGS practices. Results:. Of 2811 hospitals, 1634 (58.1%) responded; 279 (17.1%) were unable to always provide round-the-clock EGS care. Rural location, smaller bed size, and nonteaching status were associated with lack of round-the-clock care. Inconsistent surgeon coverage was the primary reason for lacking round-the-clock EGS care (n = 162; 58.1%). However, lack of a tiered system for booking emergency cases, no anesthesia availability overnight, and no stipend for EGS call were also associated with the inability to provide round-the-clock EGS care. Discussion:. We found significant gaps in access to EGS care, often attributable to workforce deficiencies.